Penerapan Akuntansi Zakat Dan Infaq/Sedekah (PSAK 109) Pada Baitul Mal Kota Langsa - Rosna Dewi; Nasrul Kahfi Lubis; Muhammad Salman (Jurnal Mahasiswa Kreatif, 2023)
This research was conducted in Baitul Mal Kota Langsa. This study aims to analyze how the application of accounting applied by Baitul Mal Kota Langsa is in accordance with PSAK No. 109. The analysis method in this study uses qualitative methods with data collection methods through interviews and documentation. The results of this study show that the application of Zakat and Infaq / Alms Accounting (Psak 109) in Baitul Mal Kota Langsa is not in accordance with the statement of Financial Accounting Standards (PSAK) Number 109 concerning Accounting for zakat and Infaq / alms which uses all components of financial statements, but Baitul Mal Kota Langsa, amil has separated between Zakat Funds and Infaq / Alms Funds in recording financial statements but the financial statements are still traditional.